(untitled) - Osborn, Anna (Thành phố Hồ Chí Minh, 2014)
To understand all the documents you come across at work you need to practise reading different kinds of text.
Keywords: English language,Tiếng Anh,Reading,English language,Tiếng Anh; Business English,Tiếng Anh thương mại,Đoc hiểu,Business English,Problems, exercises, etc.,Tiếng Anh thương mại,Câu hỏi, bài tập,vv